Structural characterization of triple transmembrane domain containing fragments of a yeast G protein‐coupled receptor in an organic : aqueous environment by solution‐state NMR spectroscopy‡. (2nd February 2015) - Fracchiolla, Katrina E.; Cohen, Leah S.; Arshava, Boris; Poms, Martin; Zerbe, Oliver; Becker, Jeffrey M.; Naider, Fred
<x xml:space="preserve">Abstract</x> This report summarizes recent biophysical and protein expression experiments on polypeptides containing the N‐terminus, the first, second, and third transmembrane (TM) domains and the contiguous loops of the α‐factor receptor Ste2p, a G protein‐coupled receptor. The 131‐residue polypeptide Ste2p(G31‐R161), TM1–TM3, was investigated by solution NMR in trifluoroethanol/water. TM1–TM3 contains helical TM domains at the predicted locations, supported by continuous sets of medium‐range NOEs. In addition, a short helix N‐terminal to TM1 was detected, as well as a short helical stretch in the first extracellular loop. Two 161‐residue polypeptides, [Ste2p(M1‐R161), NT–TM1–TM3], that contain the entire N‐terminal sequence, one with a single mutation, were directly expressed and isolated from Escherichia coli in yields as high as 30 mg/L. Based on its increased stability, the L11P mutant will be used in future experiments to determine long‐range interactions. The study demonstrated that 3‐TM domains of a yeast G protein‐coupled receptor can be produced in isotopically labeled form suitable for solution NMR studies. The quality of spectra is superior to data recorded in micelles and allows more rapid data analysis. No tertiary contacts have been determined, and if present, they are likely transient. This observation supports earlier studies by us that secondary structure was retained in smaller fragments, both in organic solvents and in detergent micelles, but that stable tertiary contacts may only be present when the protein is imbedded in lipids. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd.